HUBUNGAN PENGETAHUAN DESAIN BUSANA DENGAN HASIL MERUBAH POLA BUSANA PESTA PADA SISWA SMK NEGERI 1 PEUSANGAN BIREUEN - Flora Hutapea; Ida Lena (JURNAL KELUARGA SEHAT SEJAHTERA, 2015)
ABSTRACT This study aims to determine the relation of knowledge of fashion design with the achievement on changing the party dress model on SMK 1 Peusangan Bireuen students. The variables in this study are knowledge of fashion design and the achievement on changing party dress model. The meaning of knowledge of fashion design is the relation of student's knowledge of fashion design, while the result of changing a model of party dress is the result of students’ ability or potential on changing the party dress. The research was conducted at SMK Negeri 1 Peusangan and research subjects were all students in grade 2 and the amount of the srudents were 56 students. The methods of data collection used were knowledge of fashion design test for the variable X and the observation sheet changing the party dress model for variable Y. The data analysis technique used descriptive analysis. The results of relation of fashion knowledge test is in the middle category (29%). The test results changing model in party dress for SMK 1 Peusangan Fcalculated <Ftable is 0.235 <2.56 then there is no difference in these observations. The result of changing party dress model is at sufficient inclination level (49%). The normality test used Liliefors with the Lcalculated <Ltable or 0.0228 <0.1197 for variables X and 0.08594 <0.1197 for both variable Y is thus normally distributed variables. To test the linearity obtained Fcalculated <F table (0.83 <1.89). It can be concluded that regression equation Y = 10.04 + 0,75X is linear and Ftabel 4.02 so Fcalculated> Ftable (401.9> 4.02) are significant at α = 0.05 level. In this study used the product moment correlation formula. Based on the calculation shows that the tcalculated between X and Y at 0.924 while table = at significance level of 5% for 0.266 visible tcalculated> ttable namely (0.924> 0.266). In accordance with the criteria of acceptance and rejection of the hypothesis that working hypothesis (Ha) filed accepted. Thus it is stated that there is a relation between knowledge of fashion design with the achievement on changing party dress model. Kata Kunci : Pengetahuan desain busana dan merubah pola.